The Role of Good Corporate Governance in The Timeliness of Financial Report Presentation - Julia Safitri; Suhartini Suhartini; Suhendri Suhendri (Universitas Muhammadiyah Yogyakarta, 2023)
The first study's goal was to determine whether profitability, leverage, firm size, institutional ownership, and independent commissioners have an impact on financial reporting timeliness. The second goal was to see if the auditor class might mitigate the influence of profitability, leverage, company size, institutional ownership, and independent commissioners on financial reporting timeliness for energy businesses listed on the Indonesia Stock Exchange between 2017 and 2021. The data analysis method used logit regression for panel data analysis. According to the findings, profitability and independent commissioners had a considerable influence and a favorable link with financial reporting timeliness. Leverage, institutional ownership, and company size were not significant in the financial reporting timelines. The auditor class is unable to balance the variables of profitability, leverage, firm size, independent commissioners, and institutional ownership with financial reporting timeliness.